2018
DOI: 10.1007/s10661-018-6783-3
|View full text |Cite
|
Sign up to set email alerts
|

Climate type-related changes in the leaf micromorphological characters of certain landscape plants

Abstract: This research aimed to determine changes to some micromorphological characteristics of certain landscape plants grown in areas with different dominant climate types. Leaf samples were collected from eight woody plant species in areas with terrestrial, Black Sea, and Mediterranean climate types in Turkey. Then, scaled images of the collected leaf samples were obtained using SEM. StomaLength, StomaWidth, PoreLength, PoreWidth, and StomaDensity were determined using measurements made on the images. Data were stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Some of this variation is due to geographical location. Cetin, Sevik, and Yigit () gave a mean density of 198 per mm 2 across Turkey with individual stomata 24.29 × 16.23 μm in size. However, they varied from 298 per mm 2 , 16.55 × 9.54 μm in the temperate ecoregion (Central Anatolia) to 177 per mm 2 , 37.28 × 27.02 μm in the Mediterranean ecoregion, to 118 per mm 2 , 19.03 × 11.30 μm in the high precipitation of the Black Sea ecoregion.…”
Section: Structure and Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Some of this variation is due to geographical location. Cetin, Sevik, and Yigit () gave a mean density of 198 per mm 2 across Turkey with individual stomata 24.29 × 16.23 μm in size. However, they varied from 298 per mm 2 , 16.55 × 9.54 μm in the temperate ecoregion (Central Anatolia) to 177 per mm 2 , 37.28 × 27.02 μm in the Mediterranean ecoregion, to 118 per mm 2 , 19.03 × 11.30 μm in the high precipitation of the Black Sea ecoregion.…”
Section: Structure and Physiologymentioning
confidence: 99%
“…Some of this variation is due to geographical location. Cetin, Sevik, and Yigit (2018) Boldt and Rank (2010) found density to vary from 146 per mm 2 at the base of the crown to 321 per mm 2 in the middle and 322 per mm 2 at the top. Boldt and Rank (2010) also found that stomata can vary in size within a leaf, with 3%-10% of the stomata being "giant"-sized, reaching 25 to >40 μm long, mixed with those c. 20 μm long.…”
Section: Morphologymentioning
confidence: 99%
“…The plants indoor are affected by solar radiation. This leads to climate change in the environment as well as forest, coastal, and urban areas [38][39][40][41][42][43][44][45][46]. A recent study shows that carbon emissions affect thermal comfort and lead to climate change problems [56][57][58][59][60].…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Plants accumulate some of the heavy metals in their bodies via soil or air; and by determining the level of this accumulation, data on heavy metal pollution in soil or air can be obtained [4,12]. Therefore, the leaves of large plants [16][17][18][19], body shells [20], woods [21] and fruits [22] are used as biomonitors.…”
Section: Introductionmentioning
confidence: 99%